Kandungan Nutrisi Lumpur Sawit Hasil Fermentasi dengan Jamur P. chrysosporium - Noferdiman Noferdiman; Ahmad Yani (Agricultural Faculty, 2013)
The nutritious content fermentation of palm oil sludge by P. chrysosporiumABSTRACT. This research is aimed at observing the nutritious content of palm oil sludge fermentation by P. chrysosporium. The experimental design used completely randomized design in factorial (3 x 3). The first factor is the inoculum dosage, namely : (D1). 3 %, (D2). 6 % and (D3). 9 % of substrate weight. The second factor is the length of fermentation, namely : (L1). 4 days, (L2). 8 days and (L3). 12 days. Every treatment is repeated for three time. The data found is scrutinized by mode print and it is followed by distance test of multiple Duncan (Steel and Torrie, 1989). The variables observed in research are dry materials, crude fiber, crude protein, cellulose and lignin. The research on the influence of inoculum dosage and the length of fermentation on dry materials content and crude protein shows insignificant interaction (P0.05). On the other hand, crude fiber, cellulose and lignin show significant interaction (P0.01). The inoculum dosage of 6 % and the fermentation length of 8 days is the best combination treatment and it can reduce the crude fiber amounting to 40.86 %, an increase of crude protein amounting to 30.75 % and a decrease of cellulose and lignin amounting to 39.78 % and 36.40 % respectively.